The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.06.03.20121202
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

fMRI and Transcranial Electrical Stimulation (tES): A systematic review of parameter space and outcomes

Abstract: The combination of non-invasive brain stimulation interventions with human brain mapping methods have supported research beyond correlational associations between brain activity and behavior. Functional MRI (fMRI) partnered with transcranial electrical stimulation (tES) methods, i.e., transcranial direct current (tDCS), transcranial alternating current (tACS), and transcranial random noise (tRNS) stimulation, explore the neuromodulatory effects of tES in the targeted brain regions and their interconnected netw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 133 publications
0
9
0
Order By: Relevance
“…The MRI compatible electrodes are made from an electrically conductive rubber. It is possible that circumferential RF currents could be set up directly within these relatively large pads but for the low SAR sequences used heating is negligible, as confirmed by previous experiments (Holland et al, 2011). As a further risk mitigation strategy, in our Lab only low power imaging sequences are used.…”
Section: Safety Considerations For Tdcs In the Mri Environmentmentioning
confidence: 66%
See 2 more Smart Citations
“…The MRI compatible electrodes are made from an electrically conductive rubber. It is possible that circumferential RF currents could be set up directly within these relatively large pads but for the low SAR sequences used heating is negligible, as confirmed by previous experiments (Holland et al, 2011). As a further risk mitigation strategy, in our Lab only low power imaging sequences are used.…”
Section: Safety Considerations For Tdcs In the Mri Environmentmentioning
confidence: 66%
“…For example, one study demonstrated evidence of BOLD signal within brains of two cadavers during a concurrent tDCS and fMRI protocol (Antal et al, 2014). Whilst a previous study from our lab demonstrated visual evidence of change in echo-planar imaging (EPI) field maps that was limited to the scalp/surface near to the electrode site (Holland et al, 2011). These contrasting cases demonstrate the need for careful consideration of concurrent tDCS-fMRI data, and acquisition of appropriate field map data to allay concerns over false positive functional results from perturbation of the magnetic field.…”
Section: Safety Considerations For Tdcs In the Mri Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They highlighted that the tDCS dose effects studies had focused their attention on the current intensity range from 0mA to 2mA but saw a need to examine effects at higher doses to improve our understanding of the dose-response relationship (Batsikadze et al, 2013; Clark et al, 2012; Ho et al, 2016; Jamil et al, 2017; Zheng et al, 2011). Some studies over the last several years have expanded tDCS current intensity range up to 3mA (Agboada et al, 2020, 2019; Jamil et al, 2020) and even 4mA (Chhatbar et al, 2017), although more studies, in particular concurrent tDCS-fMRI studies, are necessary to examine relationships between stimulation dose and physiological signals (Esmaeilpour et al, 2020; Ghobadi-Azbari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 20 years, low intensity tES has been used extensively to study and modulate the neural mechanisms underlying basic physiological and cognitive processes (Bachtiar et al, 2015; Bikson and Rahman, 2013; Jamil et al, 2020; Keeser et al, 2011; Kuo et al, 2016; Minhas et al, 2010; Nitsche and Paulus, 2000; Stagg and Nitsche, 2011; Zoefel et al, 2018). Initial studies combining tES with fMRI were limited to sequential tES-fMRI recording, which primarily provides an avenue to investigate the neural mechanisms underlying tES offline (after) effects (Almeida et al, 2017; Antal et al, 2014b; Esmaeilpour et al, 2019; Ghobadi-Azbari et al, 2020; Lee et al, 2019; Meeker et al, 2019; Ruttorf et al, 2019).…”
Section: Introductionmentioning
confidence: 99%